Flow characteristics of jojoba biogasoline and its blends with regular gasoline or methanol - Ahmed T Ansari; Mamdouh T Ghannam; Emad Elnajjar; Mohamed Y.E. Selim (International Journal of Thermofluids)
The transition towards low-carbon fuels is a necessary measure against the environmental legacy of internal combustion engines, still the global network masters. Due to extensive interest in biofuels, few data about the rheological behavior of non-food-based biogasoline such as from jojoba oil are unavailable, especially for engine-related conditions. This study presents for the first time the flow characteristics of biogasoline fuel derived from jojoba oil for spark ignition engines and blended with regular gasoline or Methanol. This data gives the flow characteristics needed for further experiments or flow simulation of such new bio-gasoline from alternative sustainable source of energy for spark ignition engines. Through the transesterification process of raw jojoba oil, biogasoline is produced, a fuel grade with encouraging characteristics for spark ignition engines. A Modular Compact Rheometer Anton Paar MCR 92 was used for performing the rheological tests that imitates the conditions observed in internal combustion engines over a range of temperatures from 20 °C to 60 °C and shear rates from 10 to 100 s−1. At 20 °C and a shear rate of 20 s⁻¹, biogasoline exhibited a viscosity of 0.7 cP, decreasing to 0.4 cP at 60 °C. Blending with 15 % Methanol increased viscosity by up to 40 %, yet values remained within acceptable engine operation limits. The flow properties have been measured for blends of biogasoline with Methanol at 5 %, 10 %, and 15 % by volume and with regular gasoline at 25 %, 50 %, and 75 % by volume. The results show that at low temperatures, the viscosity of biogasoline is slightly higher than that of regular gasoline, but this difference vanishes at higher temperatures. The viscosity of biogasoline increases with the addition of more Methanol. Dynamic viscosity of biogasoline and its blends with Methanol without any other additives, is still within permissible bounds and can be used as renewable fuel for spark ignition engines without the need for engine modifications. These findings confirm that jojoba biogasoline and its blends demonstrate favorable flow behavior, remaining within acceptable viscosity limits for spark ignition engines without the need for engine modification.